Status of the Comercialize of Organic Fertilizer in the Sugamuxi Bocashi - Parra Penagos, Carlos Orlando; Herrera Rodríguez, Jenny Mairena (Cuadernos de Administración, 2009)
This article is located in “marketing” and answers the question “what is the statusof the commercialization of Bocashi Organic fertilizer in Sugamuxi? To this end,theoretical support is in the development of the mix. We find in sequence conceptualdevelopment in marketing and fertilizer as such; in turn the results arising fromsurveys applied to three definite groups and finally the analysis where the question isanswered. The article concludes with a demonstration of wastage in this sector